Student attitudes to the factors that determine the success of online teaching and the acquisition of professional skills in accounting subjects during the COVID-19 pandemic - Jovanović Dejan; Fedajev Aleksandra; Janković-Perić Marina (Nastava i Vaspitanje, 2023)
Transition to online teaching is the best approach to coping and overcoming the difficult situation that universities all over the world are facing due to the COVID-19 pandemic, as it will have the least possible negative effects on students' education and the development of professional skills. Based on the above, the primary objective of the paper is to identify the factors that influence the effectiveness of acquiring professional skills in accounting subjects in online classes during the COVID-19 pandemic as well as factors that determine the success of online teaching based on students' views. The research was conducted on a sample of 373 students from universities in Kragujevac, Belgrade, Novi Sad and Niš. Students who attended online classes in at least one accounting subject were surveyed. In the methodological sense, the analysis of the collected data was based on the application of descriptive statistics, factor analysis, and multiple regression. The research results indicate that the factors determining the success of online teaching are the adequacy, availability, and autonomy of information and communication technologies (ICT); Internet connection, advantage and simplicity of ICT use; communication with the teacher; the readiness and competence of teachers; the impact of the pandemic; online teaching flexibility and student-perceived satisfaction. In addition, it was identified that student-perceived satisfaction has the greatest impact on the development of professional skills in the accounting subject, followed by the effects of the pandemic and the adaptability of online teaching